Comparative Evaluation of Co-Crystallization Methods for the Solubility Enhancement of Poorly Water-Soluble Drug of BCS Class II - K H, Harish; D’souza, Leejoan; Nyamagoud, Sanatkumar Bharamu; Yadav, M Mahesh (Indian Journal of Pharmaceutical Education and Research)
Background: The practice of co-crystallizing 2 or more components has gained increasing popularity to create novel materials with enhanced performance and properties compared to those composed solely of pure components. Objectives: The present study is aimed to increase solubility of Piroxicam by preparing co-crystals using methods of co-crystallization using various co-formers in different solvents. Materials and Methods: The Co-crystals of Piroxicam were prepared using solvent evaporation and slow cooling methods of co-crystallization. The co-formers used in the study were benzoic acid, citric acid and PABA. The prepared Co-crystals were evaluated for solubility and dissolution rate. The Co-crystals were characterized by, Fourier Transform Infrared Spectroscopy (FTIR), Powder X-ray Diffractometry (PXRD) and Scanning Electron Microscopy (SEM). Results: The formation of co-crystals by solvent evaporation and slow cooling methods were done with benzoic acid, citric acid and PABA as co-formers and ethanol, acetone and acetonitrile as the solvent was done. It was confirmed based on melting point, PXRD data, FTIR and SEM. The aqueous solubility and dissolution rate showed improved rates as compared to pure drug. Conclusion: The prepared co-crystals showed improved rates as compared to pure piroxicam.
Keywords: Co-crystallization; Co-crystals; Improved bioavailability; Piroxicam; Slow cooling; Solvent evaporation